Efficient and Robust Molecular Solar Thermal Fabric for Personal Thermal Management. Issue 16 (12th March 2023) - Fei, Liang; Zhang, Zhao‐Yang; Tan, Yongsong; Ye, Ting; Dong, Dongfang; Yin, Yunjie; Li, Tao; Wang, Chaoxia
Abstract: Molecular solar thermal (MOST) materials, which can efficiently capture solar energy and release it as heat on demand, are promising candidates for future personal thermal management (PTM) applications, preferably in the form of fabrics. However, developing MOST fabrics with high energy‐storage capacity and stable working performance remains a significant challenge because of the low energy density of the molecular materials and their leakage from the fabric. Here, an efficient and robust MOST fabric for PTM using azopyrazole‐containing microcapsules with a deep‐UV‐filter shell is reported. The MOST fabric, which can co‐harvest solar and thermal energy, achieves efficient photocharging and photo‐discharging (>90% photoconversion), a high energy density of 2.5 kJ m −2, and long‐term storage sustainability at month scale. Moreover, it can undergo multiple cycles of washing, rubbing, and recharging without significant loss of energy‐storage capacity. This MOST microcapsule strategy is easily used for the scalable production of a MOST fabric for solar thermal moxibustion. This achievement offers a promising route for the application of wearable MOST materials with high energy‐storage performance and robustness in PTM. Abstract : A novel MOST fabric with high energy‐storage capacity and robustness is demonstrated for personal thermal management (PTM). Based on a MOST microcapsule with deep‐UV‐filter shell and encapsulated azopyrazole molecules, the MOST fabric displays ideal energy‐storage density up to 2.5 kJ m −2 and high robustness in rechargeability, washing, and rubbing.